(The Effects of Temperature, Relative Humidity, Type of Packaging on the Quality and the Shelf life of Granulated Palm Sugar) - Maman Rohaman, M; w. Fasya, Edna; Suharto, Ign (Warta Industri Hasil Pertanian, 2002)
A study on the effects of temperature,relative humidity and packaging type on the quality and storage life on the granulated palm sugar has been conducted.it was aimed at determining the storage condition to improve the granulated palm sugar shelf life. the variable applied in the study were storage temperature packaging materials and relative humidity. the observation was based on sorption isotherm method using BET model and data was processed by computer program designed in PASCAL the coorrlation among moisture content,quality and shelf life were also discussed the result showed that the stability mono layer BET of granulated palm sugar reached the moisture content level of 7.42% at 27 0C and 11.62% at 37,8 0C .the longest shelf life was 770days at 27 0C relative humidity of 6 % and using polyprophylene (pp) packaging the room temperature storage (27 oC), relative humidity of 65-80% and using polyprophylene (pp) packaging reached the shelf life of 360 days .